2011
DOI: 10.1080/14747731.2011.576844
|View full text |Cite
|
Sign up to set email alerts
|

EU Enlargement, Migration, and Asymmetric Citizenship: Political Economy of Inequality and the Demise of the European Social Model?

Abstract: This article addresses European regionalism with a focus on the viability of social citizenship and transnational migrants' and labour rights. These issues are explored by addressing two interrelated formative moments: EU enlargement towards former communist countries and the EU migration regime. The main argument is that the impact of an employerfriendly asymmetric inclusion of the new member states (NMS) into the peripheral pattern of accumulation within the EU has created severe limitations on the enactment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The E.U. rights-based regional migration regime and citizenship promised to reduce inequalities and offered empowerment and belonging (Likic-Brboric, 2012;Threlfall, 2007). It was praised for resolving the paradox between closed national borders and an open market economy (Hollifield, 2004).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The E.U. rights-based regional migration regime and citizenship promised to reduce inequalities and offered empowerment and belonging (Likic-Brboric, 2012;Threlfall, 2007). It was praised for resolving the paradox between closed national borders and an open market economy (Hollifield, 2004).…”
mentioning
confidence: 98%
“…as a project in global economic competitiveness that appeals to populist sentiments to mobilize support for exploitation of labor and speed deregulation of national labor markets (Holman, 2004). The five rounds of enlargements, particularly the 2004 round, used economic inequalities and workers from new member states to absorb shocks and crises in the old member states through discriminatory redistribution (Likic-Brboric, 2012;Liebert, 2007;Plümper & Schneider, 2007). This raises questions about how the E.U.…”
mentioning
confidence: 98%
“…Firstly, there are great disparities in income and life chances between the EU and its peripheries (Held & Kaya, 2007). In addition, social inequality -as measured by growing disparities between incomes derived from wages and investment -within Europe has remained at a persistently high level and has increased within individual member states over the past two decades (Likić-Brborić, 2011;Münch, 2012). Secondly, in general, migrants' life opportunities -as measured by risk of poverty or social exclusion -are lower than those of non-migrants.…”
mentioning
confidence: 98%
“…These are: deindustrialisation, increasing unemployment and socio-economic inequality coupled with a concomitant informalisation of the economy, a dual and segmented labour market, and precarious work and migration pressures (Likic-Brboric, 2011;Williams and Nadin, 2011). This is the general context in which the changes of industrial relations and the role of trade unions in transitional economies need to be observed.…”
Section: The Transition From a Socialist To A Market Economy And Indumentioning
confidence: 99%